2018
DOI: 10.1038/s41598-018-19800-5
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in creep life of a nickel-based single-crystal superalloy via composition homogeneity on the multiscales by magnetic-field-assisted directional solidification

Abstract: The improvement of the creep properties of single-crystal superalloys is always strongly motivated by the vast growing demand from the aviation, aerospace, and gas engine. In this study, a static magnetic-field-assisted solidification process significantly improves the creep life of single-crystal superalloys. The mechanism originates from an increase in the composition homogeneity on the multiscales, which further decreases the lattice misfit of γ/γ′ phases and affects the phase precipitation. The phase-preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 46 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…As far as the influence of a static magnetic field on solidification is concerned, there have been a great number of reports 2427 , as Ren et al . 27 briefly reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the influence of a static magnetic field on solidification is concerned, there have been a great number of reports 2427 , as Ren et al . 27 briefly reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the influence of a static magnetic field on solidification is concerned, there have been a great number of reports 2427 , as Ren et al . 27 briefly reviewed. For the present platelet immersing in the eutectic melt in the static magnetic field, the platelet with its longitude direction parallel to the direction of the Lorentz force does not imply that the c axis of the platelet can be aligned to a certain direction, some of them may be parallel while others may have certain degrees with the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…Methods have been devised to counter this, by employing solutes in grain boundaries, notably carbides to inhibit boundary sliding. A recent method adopted by [6] incorporates application of magnetic field to ensure homogeneous composition of the Nickel based super-alloy through two phases.…”
Section: Introductionmentioning
confidence: 99%
“…One such example is the work of Weili Ren et. Al (Ren et al, 2018) who found that the application of a magnetic field to the material during directional solidification of a single crystal part lead to an increase in creep life. The cause of this improvement is a combination of effects that the magnetic field have on the molten material.…”
Section: Novel Methods Of Improving Stress Rupture In Nickel Superalloymentioning
confidence: 99%
“…The result was material with better solute distribution and smaller strengthening phase precipitates more coherent with the y matrix. The use of such a magnetic field led to a reduction in the quantity of dislocations present in the material during creep and a maximum of a 5x increase in stress rupture life of the material (Ren et al, 2018).…”
Section: Novel Methods Of Improving Stress Rupture In Nickel Superalloymentioning
confidence: 99%